If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying K + -56 = 107 Reorder the terms: -56 + K = 107 Solving -56 + K = 107 Solving for variable 'K'. Move all terms containing K to the left, all other terms to the right. Add '56' to each side of the equation. -56 + 56 + K = 107 + 56 Combine like terms: -56 + 56 = 0 0 + K = 107 + 56 K = 107 + 56 Combine like terms: 107 + 56 = 163 K = 163 Simplifying K = 163
| y+5=-7x-21 | | x^2-y^2-3x+3= | | x+x+2+x+2=75 | | (x^2-2x-1)+(2a^2+2a+3)= | | 3g+2(-5+2g)=1-g | | 2(a+1)+4a=-10 | | x^2(x^2+x+1)=0 | | 8(p+1)-6p=24 | | 5(x+4)=3x+14 | | 625=(x^2)+(x^2)+6x+9 | | 9k-32=6k+8 | | x/7=5 | | 12x+7y=-35 | | x^3+125y^3= | | k+3(3)=45 | | 500-3x=275 | | 6(-1-d)=-42 | | n-10=.3n-7-.3n | | (3u+7)(6-u)=0 | | 2-11-19= | | b^4-32b^2+256= | | 70uv-91uw= | | 2x-19= | | 1/3(6z+10)= | | 7b^2+43b+40=0 | | 7(n+3)=6(n-3) | | 13t+8=4t+73 | | 2(0d-4)=2d+8 | | 5t-14=14 | | 27g+9=5g+31 | | -3(-5z+12)=-2z-36 | | 7b^2+34b+40=0 |